STRATEGI MEDIA RELATIONS POLITISI PEREMPUAN DPRD JAWA TENGAH UNTUK MEMEPERKUAT AKUNTABILITAS KERJA LEGILATIF - Yulianto, Muhammad (Program Magister Ilmu Politik, Universitas Diponegoro, 2015)
Media relations play an important and strategic role for female politicians in running their jobs as legislators in Central Java Parliament. Media has ability to drive as well as a means to realize the accountability of legislative work in order to make public aware and respond their work. Moreover, the legislators are responsible to show their accountability to the public. That is the reason why media play such important role as an agent of socialization of politiciansâ€™s work and as communication medium between politicians and their constituents. This study aims to examine female politicianâ€™s strategies and activities in media relations in order to strengthen their works accountability in Central Java Parliament. This research is a qualitative descriptive study. Data was collected by in-depth interview technique. The results showed there were two strategies media relations of the female politicians. First,Â personal strategy which is women politicians effort to build direct, communicative, and media relations, communicative and anytime media relations that produce symbiotic mutualism. Second, the institutional strategy that was facilitated by secretariat of Central Java parliament bureau build media relations between women politicians and the media or journalists to support the accountability of legislative work. Keywords: media relations, accountability, the functions of Parliament